Identifikasi Penyebab Bullwhip Effect Pada Distribusi PT Alfian Jaya Di Bali - Gagas Gayuh Aji; Amak Mohamad Yaqoub (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2015)
The purpose of the research is to identify the cause of the bullwhip effect and find solutions to overcome them. The object of research is demand and sales period of the year 2013 to 2014 on Alfian PT Jaya is. The phenomenon of the occurrence of changes in customer demand is relatively stable end of each day will be the order weekly or bi-weekly from retail company distribution center will receive orders more stable than demand faced by retail companies. Demand sole distributor will also stable, have an impact on the cost incurred by the company in storage. One way to analyze some of the causes of the bullwhip effect on the company is to analyze the factors that cause. Bullwhip value needs to be measured to determine the bullwhip effect can be done with the data aggregation method of Fransoo and Wouters.